2010
DOI: 10.1097/mca.0b013e3283368c0e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood dendritic cell counts in relation to type of coronary artery disease and brachial endothelial cell function

Abstract: This study indicates that lower blood DCs do not result from medication intake or endothelial dysfunction, and are an overall systemic effect of atherosclerosis rather than CAD type (stable or unstable) or number of stenotic coronary arteries. In view of discrete associations with cytokines, FMD, beta-blockers and statins, mDCs and pDCs seem to behave differently and may influence inflammation during atherosclerosis in different ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 26 publications
7
33
2
Order By: Relevance
“…Some studies reported unchanged counts of pDCs in patients with coronary artery disease (CAD) (Shi et al, 2007) and myocardial infarction (MI) (Wen et al, 2013). Other researchers detected decreased numbers of pDCs in patients with troponin-positive unstable coronary artery syndromes (Van Vré et al, 2006), end-stage heart disease (Athanassopoulos et al, 2004), and advanced CAD (Yilmaz et al, 2009; Van Vré et al, 2010). Furthermore, an inverse correlation between the severity of CAD and pDC numbers was observed (Yilmaz et al, 2009; Van Brussel et al, 2011).…”
Section: Proinflammatory Activities Of Pdcs In Atherosclerosismentioning
confidence: 93%
“…Some studies reported unchanged counts of pDCs in patients with coronary artery disease (CAD) (Shi et al, 2007) and myocardial infarction (MI) (Wen et al, 2013). Other researchers detected decreased numbers of pDCs in patients with troponin-positive unstable coronary artery syndromes (Van Vré et al, 2006), end-stage heart disease (Athanassopoulos et al, 2004), and advanced CAD (Yilmaz et al, 2009; Van Vré et al, 2010). Furthermore, an inverse correlation between the severity of CAD and pDC numbers was observed (Yilmaz et al, 2009; Van Brussel et al, 2011).…”
Section: Proinflammatory Activities Of Pdcs In Atherosclerosismentioning
confidence: 93%
“…The amount of circulating precursor DCs is indicative of the immune status of the organism, and decreased blood precursor DC levels have been reported in inflammation-related cardiovascular disorders. Reduced circulating precursor DC numbers in patients with atherosclerosis, myocardial infarction, or stage 3 chronic kidney disease have been associated with enhanced activation and recruitment of mature DCs in vascular lesions, infarcted areas or renal tissue [30,31,32]. Once in the tissue, DCs act as mediators of cardiovascular disease.…”
Section: Novel Immune Cell Subtypes Associated With the Development Omentioning
confidence: 99%
“…42 Several studies furthermore point toward a role of DCs in cholesterol metabolism. In mice overexpressing antiapoptotic Decreased in blood in CAD [24][25][26][27][28] Increased in unstable lesions 20,29 Decreased in blood in CAD [25][26][27][28] Present in atherosclerotic lesions 16,30 Increased in unstable lesions 16,30 Inflammatory amplifiers/ upregulation of TLR4 on cDCs/cytotoxic CD4 + T cells responses 30,31 CAD indicates coronary artery disease; cDC, classical DC; DC, dendritic cell; Flt3, factor fms-like tyrosine kinase 3; MHC, major histocompatibility complex; and pDC, plasmacytoid DC. …”
Section: Dcs Take Up Lipids and Control Cholesterol Homeostasismentioning
confidence: 99%
“…Shi et al 22 MHCII-specific T-cell activation 16,19 Type I interferon production 16 CAD indicates coronary artery disease; cDC, classical DC; CDP, common DC precursor; DC, dendritic cell; Flt3, factor fms-like tyrosine kinase 3; M-CSFR, macrophage colony-stimulating factor receptor; MDP, monocyte-DC precursor; MHC, major histocompatibility complex; pDC, plasmacytoid DC; and ?, under debate. 27 The mechanisms responsible for the decline in blood DCs in atherosclerosis may include an enhanced recruitment to lymphoid organs or sites of inflammation, as suggested by their accumulation in vulnerable lesions, 20 an increased DC turnover, or a decreased production or release from bone marrow. 37 Interestingly, decreased numbers of blood Lin −…”
Section: Circulating Dcs: Biomarkers Of Disease?mentioning
confidence: 99%